Are markers of proliferation valuable in the histological assessment of pituitary tumours? - Turner, H; Wass, J (1999)
The prediction of tumour behaviour and response to treatment has led to interest in the assessment of the proliferative potential of tumours. Pituitary tumours are usually histologically benign but are capable of aggressive growth and local invasion, although distant metastasis is limited to the very rare pituitary carcinoma. These differences in tumour behaviour may determine both the prognosis and also the effectiveness of treatment whether it be surgery, drugs or radiotherapy. Immunohistochemistry using antibodies to Ki-67 and proliferating cell nuclear antigen (PCNA) which are expressed in cells that have entered the cell cycle, can be used to assess the proportion of the cells from a tumour that are proliferating. The percentage of positively stained nuclei (labelling index (LI)) may be helpful in predicting appropriate management, as there is a relationship in many tumours between labelling index, invasiveness and tumour recurrence. This has been shown to be true for pituitary tumours, although there may be significant overlap such that low LI may be seen in the rare, aggressive, metastatic pituitary carcinomas, and high LI in indolent tumours. Thus although assessment of proliferation may be helpful in arousing suspicion as to subsequent tumour recurrence or invasiveness, this technique also demonstrates that there are other important and as yet unidentified processes that determine pituitary tumour behaviour.